Influence of activity of lubricant medium on tribochemical endurance of composition coverages - Shchepetov, V. V.; Varukhno, V. V.; Stadnichenko, V. N.; Bordujenko, L. V.; Dovgal, A. G. (Proceedings of National Aviation University (archive), 2003)
The influence of activity of lubricant medium on tribochemical endurance of composition coverages in the condition of changing velocity of slide and loading is researched